The Meaning Of Signs In Expedition Advertisement - Ni Komang Ayu Udyani; Ni Luh Sutjiati Beratha; Ni Made Suwari Antari (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2024)
Language is one way to keep relationships in harmony. People use language to communicate, convey messages verbally and directly, and express feelings. Advertisements result from a combination of communication arts with aesthetics, are persuasive, and are aimed at some parts of society. This article analyzes the meaning of verbal and visual signs on the J&T Express Advertisement. It aims to identify the verbal and visual signs and explain the meaning of the verbal and visual signs in Expedition advertisements. This analysis used J&T Express advertisement as a primary data and documentation method to collect data. This article used a qualitative method, and the data was analyzed descriptively. The results show that five data points were discussed. The verbal and visual signs analyzed used semantic theory by de Saussure to find the signifier and signified; all data have the signifier and signified. This article used Barthes' theory to analyze the meaning and find the denotative and connotative meanings. In general, verbal signs have both denotative and connotative meanings. The two verbal signs discovered in the data, all the verbal signs have denotative and connotative meaning. Two visual signs in the advertisements also convey their meanings to enhance the delivery of the value of the products.